Reliability and validity of the running anaerobic sprint test (RAST) in soccer players - Burgess, K.; Holt, T.; Munro, S.; Swinton, P. (Journal of Trainology, 2016)
Objectives: To investigate the validity and relative and absolute reliability of the Running Anaerobic Sprint Test (RAST) in ama teur soccer players. Design: Cross-sectional experimental design with an element of repeated measures. Methods: Twenty three males completed the RAST on two occasions and a Wingate test (WAnT) as criterion measure of anaero bic power. Results: Criterion validity for the RAST was strong for peak power (r = 0.70, p < 0.001) and average power (r = 0.60, p = 0.002); however, the RAST significantly underestimated peak power compared to WAnT. The RAST showed very good relative reli ability for average power, ICC = 0.88 and good relative reliability for peak power, ICC = 0.72. Assessment of absolute reliability highlighted that although when averaged across a group, test and re-test scores will be similar, when monitoring individuals an individual`s retest score may range between 0.81 and 1.2 times the original value for peak power and between 0.9 and 1.16 for average power. Conclusion: The RAST is a practicable field test to estimate levels of average anaerobic power. However, the results show that the RAST is not sensitive enough to detect strongly individual changes below 20 % and is therefore not recommended to con tinually monitor an individual`s anaerobic power. Also, if true measures of peak power are required the RAST test is limited.